2020
DOI: 10.1136/jitc-2020-001076
|View full text |Cite
|
Sign up to set email alerts
|

Avelumab for advanced Merkel cell carcinoma in the Netherlands: a real-world cohort

Abstract: BackgroundMerkel cell carcinoma (MCC) is associated with high recurrence rates and poor survival when metastatic disease is present. The immune checkpoint inhibitor avelumab has shown high response rates (RRs) and durable responses in patients with advanced MCC (aMCC) in clinical trials. To date, only results from clinical trials, patients treated in an expanded access program and very small numbers of patients have been reported. In this study, detailed real-world efficacy and toxicity data of avelumab in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
0
31
0
1
Order By: Relevance
“…Nearly all (96.4%) in our study were immunocompetent, as were patients in clinical trials [8,12,17,18]. However, proportions of patients with immunocompromised status have ranged from 6 to 30% across other real-world studies [8,9,11,12,[19][20][21]. Two of these studies investigated patients treated with avelumab.…”
Section: Discussionmentioning
confidence: 81%
“…Nearly all (96.4%) in our study were immunocompetent, as were patients in clinical trials [8,12,17,18]. However, proportions of patients with immunocompromised status have ranged from 6 to 30% across other real-world studies [8,9,11,12,[19][20][21]. Two of these studies investigated patients treated with avelumab.…”
Section: Discussionmentioning
confidence: 81%
“…Spassova et al [109] in their retrospective study found that immunocompetent patients responded better than ones with hematological malignancies or under immunosuppressive drugs, whereas the type of drug was not found to be predictor of response. Levy et al [111] showed that for avelumab, real-life data appear to be in line with results from clinical trials in terms of efficacy and toxicity. DOR in their cohort was 8.4 months, but with 43% of the patients having ongoing response at the end of the study.…”
Section: Real-life Datamentioning
confidence: 68%
“…While initial evidence is available from clinical trials, fewer real-life data are available on ICIs in MCC patients. Few authors have described experience with such drugs in MCC so far [108][109][110][111]. In the mentioned real-life studies, which comprise cohorts of patients treated with either avelumab, pembrolizumab or nivolumab plus ipilimumab, response rates ranged between 39-57%, with the best one found in a cohort of only avelumab-treated patients [111].…”
Section: Real-life Datamentioning
confidence: 99%
“…In 71% of responders, there was a durable effect of more than one year. Experience from daily practice showed higher response rates of 47–57% and complete response in almost 25% of the patients, albeit that the duration of response was shorter (median 8 months) [ 80 , 81 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Toxicities more specific for immunotherapy include autoimmune endocrine dysfunctions, pneumonitis, colitis, and hepatitis [ 86 , 87 ]. Reported overall incidence of adverse effects for avelumab was 28–46%, of which 8–9% were grade 3–4 adverse reactions [ 80 , 83 ]. In the study with pembrolizumab as first line for advanced and metastatic MCC, treatment-related adverse events of any grade occurred in 48 of 50 (96%) patients, of which 14 (28%) were grade 3 or higher.…”
Section: Treatmentmentioning
confidence: 99%